Mastering English Economic Discourse: Strategies for Russian-Speaking Economics Students - O. B. Andreeva; E. V. Pronina (Дискурс профессиональной коммуникации, 2024)
The article addresses the challenge of acquiring professional economic discourse among students pursuing a bachelor’s degree in economics. This institutional economic discourse is not merely a collection of terminological units but a complex and evolving system that exhibits a broad spectrum of genre, stylistic, and pragmatic relevance. The discourse in the economic field represents the interconnections of knowledge, various language units, and their meanings. In efforts to comprehend and elucidate economic phenomena, its practitioners employ diverse forms through which economic concepts are transformed into knowledge within an educational context. The study aims to identify effective methods for studying English-language economic discourse for students who have chosen economics as their future career. The authors utilize examples of non-codified language units from economic discourse and compared online machine-translated examples with translations produced by learners as empirical material for this research. Translating economic texts from English to Russian, editing texts translated by online translators, summarizing in English, and engaging in follow-up discussions emerged as the most effective strategies for learners to establish themselves as agents of economic discourse. These techniques ensure the comprehensive establishment, maintenance, and advancement of discourse practices. The study employs observation and analysis, logical juxtaposition, and the component analysis method. The authors conclude that the aforementioned methods for acquiring economic discourse should be given priority. This approach significantly enhances the effectiveness of converting acquired knowledge into communicative practices, transforming the discourse of the economic sphere into a dynamic tool for recreating professional expertise, with a high level of involvement from potential discourse agents in the acquisition process.